Toxoplasma gondii infection in dairy ewes: Vertical transmission and influence on milk production and reproductive performance - Klauck V.* (2016)
© 2016 Elsevier LtdThe present study aimed to evaluate the transmission of toxoplasmosis (vertical and venereal) and its influence on milk production and reproductive problems of Lacaune sheep seropositives for Toxoplasma gondii. Males and females were serologically selected using indirect immunofluorescence method in three steps of the study. Step 1: In order to evaluate the influence of toxoplasmosis on milk production, the volume of milk produced by 40 sheep (22 seronegatives and 18 seropositives for T. gondii) was weekly measured throughout the lactation period. There were no significant differences between these two groups; in other words, toxoplasmosis did not affect milk production. Step 2: In order to assess T. gondii venereal transmission, five samples of semen from seropositive rams (n = 5) were tested by endpoint and real time PCR with two days of interval; however, these semen samples were PCR negatives for T. gondii. Step 3: To evaluate reproductive problems, 12 seropositive animals out of a flock of 68 pregnant ewes showed signs of reproductive problems, such as abortion or fetal resorption. T. gondii transplacental transmission was evaluated on blood drawn from newborn lambs (n = 41), and their respective seropositive mothers (n = 30) after single, double or triple births. Serological tests showed that 65.8% of the lambs had antibodies against this protozoan, indicating a high transmission from ewe to fetus during pregnancy. Therefore, it is concluded that toxoplasmosis in sheep may impair reproduction with a high percentage of vertical transmission.